Marital Satisfaction, Communication and Coping Strategy Among Malaysian Married Couples: Factors Prediction and Model Testing - Zainul Abidin, Rozaina; Ismail, Khamsiah; Sariah Syed Hassan, Sharifah; Ahmad Sudan, Salmi (International Journal of Engineering and Technology, 2018)
Empirical evidences on the understanding of marital satisfaction as a multidimensional construct in the context of a multicultural multi-religious society are found to be limited. In this study, an attempt has been made to predict and hypothesize the factors in influencing marital satisfaction, communication and coping strategy in marriage among Malaysian married couples. Using 5-Likert scale agreement, the new Marital Satisfaction Scale has been constructed and administered among 150 respondents in a cross-sectional survey, Descriptive statistics and backward Multiple Regression Analysis (MRA) were adopted to ensure the models were estimated based on the contributions from each predictor to determine the model specification. The results have shown that the best predicted models of Marital Satisfaction and Communication are explained by 76% of variance while the prediction of Coping strategy is explained by 30% of variance. This study has recognized the usefulness of multiple regression analysis in model testing before further research on model prediction via Structural Equation Modeling is conducted. A newly hypothesized Marital Satisfaction Model was initiated by integrating the VSA Model of Marriage (Karney and Bradburry, 1995). This study is significant in contributing to pre/post-marital education and counseling fields as well as in crafting a better intervention strategy to promote a more satisfying marital institution.Â Â